Extracting Life-giving Strength from my Roots: An Endarkened Feminist (Auto)Nkwaethnography of Navigating Tenure as a Black Woman at a Predominantly White Institution. (14th October 2022) - Allen-Handy, Ayana
Abstract : This auto nkwa (life-affirming) ethnography shares a Black woman's journey to tenure at a predominantly white institution (PWI). Grounded in endarkened feminist epistemologies, the author weaves together elements of intersectionality, critical autoethnography, narrative inquiry, and Black womanist traditions to share first-person accounts of how she navigated the socio-cultural and socio-political institutional context to ultimately become the first Black woman to earn tenure in the School of Education's history at her university. In connecting the personal to theory and theory to praxis, the author illuminates how PWIs must undertake anti-racist and justice-orientations in order to fully center and support Black women's ways of knowing and being in the tenure and promotion process, ultimately ensuring their long-term success.